2022
DOI: 10.1039/d2rp00162d
|View full text |Cite
|
Sign up to set email alerts
|

Reading textual and non-textual explanations in chemistry texts and textbooks – a review

Abstract: Reading is an integral part of chemistry education. The language of chemistry plays a major role when reading chemistry texts and textbooks. Reading textual and non-textual explanations impact students’ understanding...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 128 publications
0
1
0
Order By: Relevance
“…Within the area of chemistry education, recent research studies investigating chemistry textbooks have focused on several aspects conveyed in textbooks including chemical representations (Akaygun, 2018;Demirdoğan, 2017;Farida et al, 2018;Upahi & Ramnarain, 2019), usage of analogies (Şendur et al, 2011), assessment and evaluation approaches (Gültekin & Nakiboğlu, 2016), the acquisition of content and scientific skills (Koray et al, 2006;Şen & Nakiboğlu, 2012), science textbook tasks (Bakken & Andersson-Bakken, 2021;Vojir & Rusek, 2022), textual and non-textual explanations (Meyer & Pietzner, 2022) and the practical work representations (Chen & Eilks, 2019). It is important for chemistry educators to know how each of these aspects are given in the textbooks for future planning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the area of chemistry education, recent research studies investigating chemistry textbooks have focused on several aspects conveyed in textbooks including chemical representations (Akaygun, 2018;Demirdoğan, 2017;Farida et al, 2018;Upahi & Ramnarain, 2019), usage of analogies (Şendur et al, 2011), assessment and evaluation approaches (Gültekin & Nakiboğlu, 2016), the acquisition of content and scientific skills (Koray et al, 2006;Şen & Nakiboğlu, 2012), science textbook tasks (Bakken & Andersson-Bakken, 2021;Vojir & Rusek, 2022), textual and non-textual explanations (Meyer & Pietzner, 2022) and the practical work representations (Chen & Eilks, 2019). It is important for chemistry educators to know how each of these aspects are given in the textbooks for future planning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a recent review by Meyer & Pietzner (2022), the influence of textbook language and reading was assessed. The review revealed that these aspects have primarily been investigated in relation to the understanding of concepts and non-textual explanations, with recent growth in the exploration of these non-textual aspects.…”
Section: Introductionmentioning
confidence: 99%